Estimating wolf abundance with unverified methods - Adrian Treves; Francisco J. Santiago-Ávila (Academia Biology)
Wildlife abundance can be very difficult to estimate, especially for rare and elusive species, such as wolves. Over nearly a century, wolf scientists have developed methods for estimating abundance across large areas, which involve marked animals being detected again after capture, sometimes supplemented by observations of the associates of those marked animals. Recently, several US jurisdictions have departed from those proven methods to explore alternatives that are believed to be less expensive for wolf populations estimated >1000 individuals. The new methods sacrifice precision but are believed to retain adequate accuracy and sensitivity to changing conditions for reliable decision-making. We review evidence for the accuracy, precision, sensitivity, and reproducibility of the new “scaled occupancy model” (SOM) applied in Wisconsin. We conclude that the Wisconsin method would systematically overestimate wolf abundance by large (but currently incalculable) margins. Because Wisconsin, similar to other states, not only changed to unverified methods but also implemented widespread wolf-killing, shortcomings in their estimates of wolf abundance may have far-reaching consequences for population viability and confidence in state wildlife policy. We discuss findings from Wisconsin alongside similar findings for other states’ occupancy models being insensitive to human causes of mortality that have recently increased. Overall, Wisconsin’s method for estimating wolf abundance shows significant departures from best practices in scientific measurement. Verification will require independent replication and unbiased tests at multiple scales in multiple habitats under different human-induced mortality rates and rigorous independent review before the new methods are considered reliable.